Developing a STEAM-Based Water Cycle Diorama Integrating 3D Printing, Virtual Reality, and Local Wisdom: An Educational Design Research - Rosmalah Yanti; Purwo Susongko; Dyah Rini Indriyanti (Proceedings of International Conference on Science, Education, and Technology, 2026)
The water cycle is a core topic in elementary IPAS learning, but students often find it difficult because several processes are abstract, dynamic, and not directly observable. This study develops a conceptual design for SIAR Media, a STEAM-based water cycle diorama integrating 3D printing, Virtual Reality (VR), and the local wisdom of the Tongkonan Traditional House. Using Educational Design Research, the study focuses on two initial phases: analysis and exploration, and design and construction. Participants included three elementary school teachers and nine fifth-grade students, while conceptual validation involved subject matter and media experts. Data were collected through semi-structured interviews, literature review, and expert validation, then analyzed thematically and descriptively. Findings show that students recognize basic water cycle stages but still struggle to explain condensation, infiltration, and causal relationships among water cycle components. Teachers also reported that existing media remain limited in connecting concrete objects with invisible scientific processes. The resulting design combines a 3D-printed physical diorama, VR visualization, STEAM-oriented activities, local cultural context, and learning scaffolds. Expert feedback confirms its pedagogical relevance and recommends stronger visualization of process relationships and explicit engineering and mathematics activities.